Selective removal of fluorinated tin oxide (SnO2:F) from Pilkington TEC glass - Rekow, Mathew, author; Sampath, Walajabad, advisor; Sites, James, committee member; Radford, Don, committee member (Colorado State University. Libraries, 2017)
High power lasers are utilized in a variety of processes in solar energy production and energy storage. In the production of CdTe (Cadmium Telluride) solar cells, pulse lasers are used for the so called P1 scribe step that is the first step in process of creating discrete series connected cells on an otherwise monolithic glass panel. A standard laser process sequence is well established in the industry. The common P1 process step removes all previously deposited materials, resulting in exposure of the soda lime glass substrate along the scribe line. These previously deposited layers include three layers deposited during the fabrication of the glass panel, an intrinsic SnO2 layer, a SiO2 layer, and the conductive SnO2:F layer, the latter of which forms the transparent conductive front contact of the solar cell. If the CdTe film is applied immediately afterward, sodium diffuses from the glass into the deposited CdTe film and is detrimental to the performance of the CdTe solar cell (1). To mitigate this problem, commercial processes perform the P1 scribe after CdTe deposition and the resulting groove is filled with a photo-resist. This photo-resist application process accounts for a significant fraction of the capital equipment cost in a CdTe solar panel production line (2). A means of creating a Na barrier layer in situ would eliminate the requirement of the photo-resist application step and simplify the production process. This work is aimed at developing a laser based scribe process that removes the SnO2:F layer but preserves the intrinsic SnO2 layer and the SiO2 layer to serve as a barrier to Na diffusion and hence eliminate the need for the photoresist application step. During this work, a very unusual laser-material interaction was discovered where the laser appears to initiate a physical – chemical reaction that proceeds along an unusual and apparently undescribed pathway that has many of the characteristics of an etch process. This laser "etching" mechanism allows arbitrary reduction of the film thickness in a controlled manner on the scale of a few microns. In addition to the fine depth selection, we find that there develops a laser pulse duration dependent microstructure on the surface. The unusual characteristics of this interaction are examined and a physical model is proposed to describe it. Finally, sodium diffusion effects were measured and other potential applications of this novel process are explored.
Keywords: CdTe; scribe; tin oxide; pulse laser; ablation; solar cells